THE ANALYSIS OF INDONESIAN ECONOMIC AND GLOBAL UNCERTAINTY: A VECTOR AUTO REGRESSION APPROACH - Darwis Muhammad Ahrori; Lucik Lucik (UPT Penerbitan Universitas Jember)
The global economic uncertainty paradigm is part of the issue of VUCA World in recent years. Several studies on uncertainty were developed to understand the global dynamics and the spillover impacts in order to anticipate the global turmoil. One of the proxies used to show economic uncertainty is the Economic Policy Uncertainty (EPU) index Introduced by Baker et al (2015). This study aims to Be Able to know the impact of spillover from the global economic uncertainty on the economy in Indonesia as measured by Gross Domestic Product (GDP). The VAR analysis method is used to review the dynamics of the GDP turmoil that Occurs due to the shock of global uncertainty. Variables in the models are estimated at 1st difference to satisfy stationary Assumptions. Cointegration test results show a long-term relationship between the Indonesian economies, with global uncertainty. The global cointegration models of Indonesia's GDP shows that Indonesia is not significantly affected by the turmoil of global changes. The conclusion in this study is that global uncertainty does not directly give a shock effect on the Indonesian economy.